Microplastics cause neurotoxicity and decline of enzymatic activities in important bioturbator Hediste diversicolor. (July 2022) - Urban-Malinga, Barbara; Jakubowska-Lehrmann, Magdalena; Białowąs, Marcin; Hallmann, Anna
Abstract: Microplastics (MPs) tend to accumulate in marine sediments thus benthic fauna is particularly vulnerable to microplastic pollution. Hediste diversicolor is a widespread species in coastal marine sediments. It plays key ecological functions mostly related to bioturbation process which means sediment reworking due to the worm burrowing activity and building a network of galleries. Herein, we show that commercial plastic microspheres of two sizes (63–75 and 300–355 μm) have the potential to cause neurotoxicity in H. diversicolor . The whole-body acetylcholinesterase (AChE) activity – a common indicator of neurotoxic effect - was on average 60% lower in polychaetes exposed for 28 days to MPs served at environmentally relevant concentrations (0.08% sediment d. wt.), than in unexposed ones. Significantly reduced activities of antioxidant enzymes (SOD, CAT, GST) indicated suppression of the cellular antioxidative system in worms exposed to MPs . No changes were, however, observed in tGSH, lipid or protein oxidation measures (CBO, MDA), and in the energetic value of these polychaetes. The response was generally similar with no regard to MPs size. Only very few microspheres were found in polychaetes exposed to MPs spiked sediment. The potential role of MPs-associated pollutants as a factor responsible for observed biochemical effects, is discussed. Highlights: 60% lower AChE activity in H. diversicolor exposed to MPs-spiked sediments. Significant suppression of antioxidant enzymes. No effect on worm energy reserves.